Determining the limiting factor of the electrochemical stability window for PEO-based solid polymer electrolytes: main chain or terminal –OH group?. Issue 5 (9th April 2020) - Yang, Xiaofei; Jiang, Ming; Gao, Xuejie; Bao, Danni; Sun, Qian; Holmes, Nathaniel; Duan, Hui; Mukherjee, Sankha; Adair, Keegan; Zhao, Changtai; Liang, Jianwen; Li, Weihan; et al.
Abstract : Terminal –OH group in PEO-based solid polymer electrolytes is the limiting factor of the electrochemical stability window, replacing it with more stable groups can accelerate the development of high-voltage solid-state batteries. Abstract : Due to higher energy density, high-voltage all-solid-state lithium batteries (ASSLBs) have attracted increasing attention. However, they require solid-state electrolytes (SSEs) with wide electrochemical stability windows (ESW, typically >4.2 V) and high-stability against the Li anode. Nevertheless, poly(ethylene oxide) (PEO), the most widely used solid polymer electrolyte (SPE), can't tolerate a high-voltage over 4 V. Whether the main chain (–C–O–C–) or the terminal hydroxide group (–OH) is the limiting factor for the narrow ESW remains unknown. Herein, poly(ethylene glycol) (PEG) and poly(ethylene glycol)dimethyl ether (PEGDME) with different terminal groups are selected to answer this question. The results show that the reactive terminal –OH group is the limiting factor towards applicability against high voltage and the Li anode. Replacing –OH with more stable –OCH3 can significantly extend the ESW from 4.05 to 4.3 V, while improving the Li-anode compatibility as well (Li–Li symmetric cells stably run for 2500 h at 0.2 mA cm −2 ). Its practical application is further proved by developing PEGDME-based ASSLB pouch cells. The 0.53 mA cm −2 Li–LiFePO4 and 0.47 mA h cm −2 Li–LiNi0.5 Mn0.3 Co0.2 O2 cells demonstrated high capacity retention of 97% and 90% after 210 cycles and 110 cycles, respectively. This work offers a new strategy for PEO-based high-voltage ASSLB development by changing the unstable terminal groups.